The Influence of Traditional Games and Gender on Children’s Motoric Physical Development - Diyenti, Adella Kharisma; Rakimahwati, Rakimahwati (Universitas Negeri Semarang, 2019)
This research on traditional games discusses that are passed down from generation to generation, which has to disappear and is unknown to children today. Traditional games began to shift to playing patterns at home not to develop a child’s physical motorbike. The purpose of this study is to renew traditional games and gender in children’s physical motor development. The subject of this study consisted of 60 kindergarten children at Mutiara Bunda Kindergarten, fifty city district. The experimental research data method was obtained by using this pre-test-posttest experimental research observation and data collection techniques using 2x2 factorial design, using validity, reliability, normality test, 2-way ANOVA test. The results of this study regarding the motorists of the physical development of boys were higher with an average number of 78.9, 77,4women, overall women, a significant overall number of traditional games and gender in physical development in children of the mother-of-kindergarten pearls.